SYNTHESIS, CHARACTERIZATION AND MODIFICATION OF FLEXIBLE POLYURETHANE FOAMS USING RAW MATERIALS FROM BIOPOLYOLS BASED ON PALM OIL AND OTHER VEGETABLE OILS: A REVIEW - Neswati Neswati; Novizar Novizar; Syukri Arif; Yusniwati Yusniwati (Jurnal Agroindustri, 2019)
Flexible polyurethane foams is the most produced foam compared to other types of polyurethane foams. The raw material for polyurethane foams is usually derived from petroleum polyols. The availability of petroleum which is getting thinner needs to be sought alternative raw materials for polyurethane foams from vegetable polyols (biopolyols). The relatively high productivity of palm oil causes the potential of palm oil to be used as raw material for flexible polyurethane foams compared to other vegetable oils. Various formulations and modifications that have been made in synthesizing flexible polyurethane foams from various types of biopolyols are aimed at increasing the usability and to produce flexible polyurethane foams with characteristics close to polyols made from petroleum-based foams.Busa poliuretan fleksibel merupakan busa yang paling banyak diproduksi dibanding dengan jenis busa poliuretan yang lain. Bahan baku busa poliuretan biasanya berasal dari poliol minyak bumi. Semakin berkurangnya ketersediaan  minyak bumi,  maka perlu dicari alternatif  bahan baku busa poliuretan dari poliol nabati (biopoliol). Produktivitas kelapa sawit yang cukup tinggi menyebabkan minyak kelapa sawit cukup potensi digunakan sebagai bahan baku busa poliuretan dibandingkan dengan minyak nabati lain. Berbagai formulasi dan modifikasi yang telah dilakukan dalam mensintesis busa poliuretan fleksibel  dari berbagai jenis biopoliol  bertujuan untuk meningkatkan daya guna dan untuk menghasilkan busa poliuretan fleksibel dengan karakteristik mendekati busa berbahan baku poliol dari minyak  bumi.